Cloning and expression of miniaturized haloalkane dehalogenase enzyme - Lee, Ser Leng (2015)
Haloalkane dehalogenase (HLD) belongs to a group of hydrolases class of enzymes that catalyses the hydrolysis of haloalkanes. Haloalkane dehalogenases are useful for many bioremediation applications. Mini proteins design of less than 100 amino acids residues are a subject of interest as they confer better stability, has a minimized loss of entropy and the structures are easier to study. In this study, the design of a minimized structure from DhaA haloalkane dehalogenase was done to obtain a functional protein with a smaller structure. A 60 residues amino acids structure was designed from 296 residues through structural modelling with YASARA software. Through homology modelling, docking and molecular dynamics (MD) simulation, the 3D structure of the mini protein was designed, cloned, expressed in pET32b vector, and transformed to E. coli transformants. Protein expression was optimized at 20 °C and inducer concentration of 0.01 mM. The kinetics of the mini protein were analysed with Isothermal Titration Calorimetry (ITC) method and it was found out that the mini protein had some interactions with various substrates concentration. At a much lower efficient protein as compared to the native structure, it is recommended that further modifications of protein should be done to achieve better functionality.